Rigid Bronchoscopy - Diaz-Mendoza, Javier; Peralta, A. Rolando; Debiane, Labib; Simoff, Michael J. (Seminars in Respiratory and Critical Care Medicine, 2018)
Rigid bronchoscopy is one of the oldest medical techniques used in the respiratory and thoracic fields. Even though its use declined after the development of flexible bronchoscopy, it has again gained importance with the growth of interventional pulmonology, becoming a critical technique taught as part of the training in this subspecialty. The therapeutic advantages compared to other approaches of thoracic pathologies makes rigid bronchoscopy a primary component in the present and future of interventional pulmonary medicine.
Keywords: rigid bronchoscopy; flexible bronchoscopy; airway stents; tracheal stenosis; cryotherapy; laser; electrocautery